2010
DOI: 10.1142/s0192415x10007737
|View full text |Cite
|
Sign up to set email alerts
|

Stachydrine, a Major Constituent of the Chinese Herb Leonurus Heterophyllus Sweet, Ameliorates Human Umbilical Vein Endothelial Cells Injury Induced by Anoxia-Reoxygenation

Abstract: Stachydrine is a major constituent of Chinese herb leonurus heterophyllus sweet, which is used in clinics to promote blood circulation and dispel blood stasis. Our study aimed to investigate the role of stachydrine in human umbilical vein endothelial cells (HUVECs) injury induced by anoxia-reoxygenation. Cultured HUVECs were divided randomly into control group, anoxia-reoxygenation (A/R) group and 4 A/R+stachydrine groups. HUVECs in the control group were exposed to normoxia for 5 hours, while in all A/R group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…We previously reported that L. sibiricus reduced the uterine bleeding volume in RU486-induced abortion efficiently (Li et al, 2011) ; however, the active constituents and the mechanism by which L. sibiricus reduces uterine bleeding are poorly understood. Stachydrine hydrochloride (C 7 H 13 NO 2 Á HCL) is the major constituent of L. sibiricus, and has low toxicity and high safety (Yin et al, 2010). Therefore, stachydrine hydrochloride is regarded as a candidate for reducing the volume of uterine bleeding in RU486-induced abortion.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that L. sibiricus reduced the uterine bleeding volume in RU486-induced abortion efficiently (Li et al, 2011) ; however, the active constituents and the mechanism by which L. sibiricus reduces uterine bleeding are poorly understood. Stachydrine hydrochloride (C 7 H 13 NO 2 Á HCL) is the major constituent of L. sibiricus, and has low toxicity and high safety (Yin et al, 2010). Therefore, stachydrine hydrochloride is regarded as a candidate for reducing the volume of uterine bleeding in RU486-induced abortion.…”
Section: Introductionmentioning
confidence: 99%
“…This compound, which displays interesting biological activities, is a chief constituent of the Chinese herb, Leonurus heterophyllus Sweet and is used in clinics practising traditional Chinese medicine to promote blood circulation. Yin et al, 2010, report that their cell culture study indicated that stachydrine ameliorated human umbilical vein endothelial cell injury induced by anoxia-reoxygenation, with the putative mechanism being cited as related to the inhibition of tissue factor expression.…”
Section: )mentioning
confidence: 99%
“…Stachydrine exhibits low toxicity, with multiple, long-term oral doses failing to produce any toxic reactions, although intramuscular injections of solutions of the herb can cause a dry mouth and shortened sleep. 43 Stachydrine, at low doses, inhibits hydrogen peroxideinduced myometrial smooth muscle cell apoptosis by upregulating Bcl-2 expression. 44 Yin et al 43 reported that stachydrine attenuated ROS production and inflammation and subsequently reversed changes in SOD, GPx, MDA and endothelin-1, thus ameliorating the decline in the viability of human umbilical vein endothelial cells and the enhanced lactate dehydrogenase (LDH) activity that occurred during anoxia-re-oxygenation.…”
Section: Stachydrinementioning
confidence: 99%
“…43 Stachydrine, at low doses, inhibits hydrogen peroxideinduced myometrial smooth muscle cell apoptosis by upregulating Bcl-2 expression. 44 Yin et al 43 reported that stachydrine attenuated ROS production and inflammation and subsequently reversed changes in SOD, GPx, MDA and endothelin-1, thus ameliorating the decline in the viability of human umbilical vein endothelial cells and the enhanced lactate dehydrogenase (LDH) activity that occurred during anoxia-re-oxygenation. Moreover, stachydrine has been shown to exert anti-oxidant effects by reducing plasma LDH activity and MDA levels in animal models of acute myocardial ischaemia.…”
Section: Stachydrinementioning
confidence: 99%